Para que serve a EBC? : a configuração de um problema público a partir do desmonte da Empresa Brasil de Comunicação - Priscila Martins Dionizio (2022)
Since 2016, with the impediment of democracy organized through the destitution of President Dilma Rousseff (PT), the Empresa Brasil de Comunicação (EBC) goes through a process of erosion of its political autonomy and its incipient mechanisms of social control. With ongoing structural changes, a problematic situation starts to unfold around the company. Political actors, institutions, EBC staff, movements that advocate for the democratization of communication and the corporate media seek interpretive frameworks in order to comprehend and evaluate the EBC and its role in democracy. Values such as public interest, citizenship, autonomy, freedom of speech, social control and plurality collide with discourses of austerity and the diminishing of the State which seeks to label the EBC as inefficient, expensive,corrupted and, at last, unnecessary for Brazilian society. Through an interpretive approach, built on the support of the sociology of public problems, this work maps the discussion related to the EBC that emerged between May 2016 and December 2019. This project focuses on three arenas: press coverage, virtual mobilizations and the National Congress. By mapping these arenas, we identified different constructions of the problem around EBC and the affected and mobilized publics that work in this circumscription, as well as solutions pointed to the provision of public media service in Brazil, and frameworks structuring interpretations of the discussion.A dynamic of attack and defense of the EBC marks the configuration of the arenas, from the mobilization of superficial and/or false information, on the one hand, to the attempt to valorize the public media, on the other. This reactive dynamic conditions the configuration and development of the public problem around the EBC. Three major frameworks shape the discussion: a) the reduction of the role of the state and democracy to the instrumental principles of efficiency and rationalization; b) the antagonism promoted between public versus private communication, which creates value for public media in opposition to the presumed effects of massive corporate media; c) and that of an equivalence created between public communication and democracy, which leads the discussion to generic values and principles, leaving vague formulations about the public media service and the potential of the EBC. The need to develop a language capable of elaborating and unfolding, in a more concrete and less idealized way, the place of a public media service in a media ecosystem that is not only oligopolized, but also hybrid, hyperconnected and with different platforms and environments is indicated as a possible way out and as a collective task.